The Role of Cloud-Based Accounting in Enhancing Operational Efficiency of MSMEs - Edi Purwanto; Dorit Hartini; Finarsih Septeia; Afriani Pravitasari (Lembaga Pengembangan Kinerja Dosen, 2025)
In the era of digital transformation, the adoption of cloud-based accounting has emerged as a strategic solution to enhance the operational efficiency of Micro, Small, and Medium Enterprises (MSMEs). This study aims to examine the role of cloud-based accounting in improving operational efficiency and to identify the mediating and moderating factors that influence this relationship. Using a quantitative approach, data were collected from 220 MSME respondents across various sectors in Indonesia. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. The results reveal that cloud-based accounting adoption significantly and positively affects operational efficiency by reducing processing time, minimizing costs, and increasing accuracy in financial management. Furthermore, digital literacy and organizational readiness are found to be strong predictors of adoption, while perceived usefulness and ease of use mediate the impact of adoption on efficiency. The study integrates the Technology Acceptance Model (TAM) and Technology–Organization–Environment (TOE) frameworks, providing both theoretical and practical insights. These findings suggest that MSMEs should strengthen their digital competencies and infrastructure readiness, while policymakers and software providers should promote inclusive digital transformation programs to maximize the benefits of cloud accounting for MSME sustainability.